RETRACTED: Kewirausahaan masyarakat perkebunan Dieks Afdeling Malang - Kasimanuddin Ismain; Moch Nurfahrul Lukmanul Khakim; Liska Novianti Paramitaswari (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2023)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S) to article entitle “Kewirausahaan masyarakat perkebunan Dieks Afdeling Malang” Vol. 3, No. 1 (2023), DOI: http://dx.doi.org/10.17977/um063v3i12023p29-39. This paper has been found to be in violation of the Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S) publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in International Journal of Social Sciences and Education, Vol. 3, No. 2 (2022), DOI: https://doi.org/10.26858/ijosse.v3i2.42450. The document and its content has been removed from Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S) and a reasonable effort should be made to remove all references to this article.